Conflict of laws in arbitration - Ting, Hie Ching (2012)
Generally, arbitration is preferred as an effective method of settling disputes between the parties which are from different countries. Conflict of laws is a part of English law that we will use whenever we face a legal problem which has a foreign element in it. Conflict of laws is defined as a conflict between the laws of two or more states or countries that would apply to a legal action in which the underlying disputes, transaction or event affects or has a connection to those jurisdictions. This research is on conflict of laws in arbitration. The objective of this study is to determine the grounds to solve conflict of laws in arbitration. This study covers the legal cases in England which are related to conflict of laws in arbitration. The methodology of this study has been based on documentary analysis. The research findings show that the grounds to solve the conflict of laws in arbitration are jurisdiction, choice of law and enforcement and recognition of foreign judgment. The court must have jurisdiction to settle the dispute as provided in the agreement signed between both parties. When there was an express or implied choice of law in arbitration, the parties would apply the law as expressed in the agreement. However, in the absence of express or implied choice of law, the parties would apply English conflict of laws rules to determine the dispute. The English court would recognize and enforce the foreign judgment if the judgment was final and conclusive.